2015
DOI: 10.1002/rcm.7300
|View full text |Cite
|
Sign up to set email alerts
|

Fast screening of analytes for chemical reactions by reactive low‐temperature plasma ionization mass spectrometry

Abstract: LTP in this study serves both as an ambient ionization source for analyte identification (including reagents, intermediates and products) and as a means to produce reagent ions to assist gas-phase ion/molecule reactions. The present reactive LTP-MS method enables fast screening for several analytes from several chemical reactions, which possesses good reagent compatibility and the potential to perform high-throughput analyte screening. In addition, with the detection of various reactive intermediates (intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…LTP has been widely applied to the analysis of petroleum, explosives, agrochemicals, fatty acid esters and drugs . In some cases, employing amine substances as reactants in LTP‐MS has helped to improve the ionization efficiency of analytes containing carbonyl groups . For example, methylamine, an accessible amine source, was used in our recent reactive LTP‐MS study of ketone‐based organic UV filters and showed the best performance characteristics of all tested amine and ammonium compounds …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTP has been widely applied to the analysis of petroleum, explosives, agrochemicals, fatty acid esters and drugs . In some cases, employing amine substances as reactants in LTP‐MS has helped to improve the ionization efficiency of analytes containing carbonyl groups . For example, methylamine, an accessible amine source, was used in our recent reactive LTP‐MS study of ketone‐based organic UV filters and showed the best performance characteristics of all tested amine and ammonium compounds …”
Section: Introductionmentioning
confidence: 99%
“…43 In some cases, employing amine substances as reactants in LTP-MS has helped to improve the ionization efficiency of analytes containing carbonyl groups. 44,45 For example, methylamine, an accessible amine source, was used in our recent reactive LTP-MS study of ketone-based organic UV filters and showed the best performance characteristics of all tested amine and ammonium compounds. 46 In this paper, a reactive LTP-MS method is introduced that allows for the detection of neurosteroids in brain tissue.…”
mentioning
confidence: 99%
“…The signal at m/z 290, tentatively assigned as the protonated final imine, was clearly observed. The peak at m/z 273 was reported by the loss of NH 3 from the final imine . This may be due to the fragmentation of the final imine ( m/z 290) during ionization.…”
Section: Resultsmentioning
confidence: 99%
“…The Schiff‐base refers to the reaction between a class of compounds containing aldehydes (or ketones) and amino groups. The reaction generates a typical adduct intermediate which subsequently converts to an imine group (―C═N―) with the loss of 1 molecule of water …”
Section: Resultsmentioning
confidence: 99%
“…53 DART detection of organometallic compounds have involved some similar experiments by mixing the ligand and metal together prior to sampling, 77,78 and gas phase chemical reactions have been induced by low temperature plasma, 79,80 showing the potential for host-guest supramolecular chemistry with DART. Drawing from these experiments, we introduce the concept of using host-guest based supramolecular complexation chemistry directly in the gas phase, termed here reagent assisted desorption ionization (RADI), specically for the enhanced detection of neurotransmitters.…”
mentioning
confidence: 99%